Development and histogenesis of human foetal lung in relation with gestational age - Naik, K. Satheesh; Madhavi, K.; Gurushanthaiah, M.; Mahesh, G. M. (International Journal of Research in Medical Sciences, 2017)
Background:The objective was to study the development and histogenesis of human foetal lung in relation with different gestational age. Methods:In the present study lung specimens were collected from formalin fixed 27 aborted foetuses (14 male, 13 female) by abdominal dissection between 6 weeks to 40 weeks of gestational age. Results:In the present study we observed that there was a delay in the appearance of embryonic, pseudo glandular phase, canalicular, terminal saccular and alveolar stages of the lung. Conclusion:Delay in the developmental anatomy and histogenesis of the lung cells leads to histopathological abnormalities which gives knowledge to the clinicians during clinical procedures.